Prebiotic effect of spices, herbs and Thai curry under in-vitro digestion on attachment of probiotic bacteria on large intestine Caco-2 cells - Klinsoda, Jutamat; Yodin, Kanokwan; Treesuwan, Khemmapas (Agriculture and Natural Resources, 2024)
Importance of the work: Little information is available on the prebiotic properties of spices or herbs in Thai curries after digestion and their interaction with probiotic microbiota. Objectives: To investigate the in-vitro viability and adherence to Caco-2 cells of selected probiotics presenting in human and commercial products (Lactobacillus acidophilus, Lactobacillus casei and Bifidobacterium bifidum) after inoculation in 14 spice or herb extracts and 8 Thai curries and passing through an in-vitro digestion model. Materials and Methods: The selected probiotics were passed in the in-vitro digestion model and further evaluated for large intestine Caco2-cell adhesion. Results: In total, 14 spice or herb extracts (chili, garlic, galangal, turmeric, shallot, lemon grass, basil, red cotton tree flowers, cloves, coriander root, cumin, shrimp paste, cinnamon and finger root) and Thai curries had no inhibitory effects on the selected probiotics. L. casei inoculated in Nam Ngeaw curry had the greatest Caco-2 cell adhesion (2.37%), whereas L. casei was lower after exposure to turmeric extracts (0.27%; p < 0.05). The adhesion of L. acidophilus in Gaeng Aom and Nam Ngeaw curries was similar to the control, whereby L. acidophilus after exposure to other spice/herb extracts and curries lost adherence (p < 0.05). There were no significant differences in adherence to Caco-2 cells of B. bifidum incubated in the Thai curries, with the adhesion of B. bifidum being lower in garlic extract compared to coriander root extract (p < 0.05). Main finding: The screening results of the spice or herb extracts and mixed spices/herbs in Thai curries was able to reveal their prebiotic properties to support Caco-2 cell adhesion of probiotics after ingestion.